Balance of payments crises timing the collapse of the Philippine peso - Majuca, Ruperto II (1992)
The focus of this paper is to undertake an empirical analysis of the Philippine balance of payments and to predict the date of the exchange rate collapse. Domestic credit expansion stimulated speculative attacks against the peso leading to the eventual depletion of the Central Bank's stock of foreign reserves.
Keywords: Balance of payments; Foreign exchange reserves